Stimuli-responsive protein-based micro/nano-waveguides. Issue 95 (15th October 2015) - Hou, Zhishan; Sun, Siming; Zheng, Boyuan; Yang, Ruizhu; Li, Aiwu
<x xml:space="preserve">Abstract</x> Protein-based single nano-wire waveguides constructed by FsLDW using BSA aqueous ink which might be applicable for uses as sensing probes.